2020
DOI: 10.3390/su12031081
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Emergency Management Based on Intelligent Information Processing

Abstract: In this paper, we introduce how to identify, rank, evaluate, and respond to risks based on intelligent information processing, providing new ideas and research directions for sustainable emergency management. First, we discuss the contributions and deficiencies of the existing research that have informed the development and launch of this Special Issue and, second, we provide an overview of the three articles included. In addition, this article introduces this particular Special Issue, not only to complement t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…In this battle of epidemic prevention and control, Chinese universities have provided significant support and made remarkable achievements in epidemic control and social stability. The outbreak has set new requirements for sustainable risk management (Luo et al 2020). For Chinese universities, these requirements have arisen primarily in the following areas.…”
Section: Challengesmentioning
confidence: 99%
“…In this battle of epidemic prevention and control, Chinese universities have provided significant support and made remarkable achievements in epidemic control and social stability. The outbreak has set new requirements for sustainable risk management (Luo et al 2020). For Chinese universities, these requirements have arisen primarily in the following areas.…”
Section: Challengesmentioning
confidence: 99%
“…More recently, and with reference to epidemic emergencies, Qiu et al (2018) demonstrated how an open attitude and active engagement of stakeholders to address risk information needs can build trust and facilitate collaborations, whereas Perry and Laws (2020) developed a collaborative planning and shared decision making framework for risk informed decision making in biosecurity. A number of studies have also investigated the adoption of digital technologies to enhance emergency management ( Gasmelseid, 2014 ; Luo et al, 2020 ; Misra, Roberts and Rhodes, 2020 ; Yang, Yang and Plotnick, 2013 ).…”
Section: Epidemic Management As Emergency Managementmentioning
confidence: 99%
“…In December 2019, a new virus outbreak occurred and has not been under complete control. Therefore, we initiated research on this new pneumonia virus to predict its duration, infections, death toll, and the impact on China's economy for risk assessment, based on intelligent information processing methods (Luo et al 2020).…”
Section: Introductionmentioning
confidence: 99%